PENEGAKAN HUKUM WAJIB MENYALAKAN LAMPU UTAMA PADA SIANG HARI BAGI SEPEDA MOTOR RODA DUA MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI SATLANTAS POLRESTA PEKANBARU - Pratama, Wira Andika; Heriyanti, Yuli; Akbar Novi Maimory, Aminoel (Jurnal Pahlawan, 2024)
Article 107 paragraph (2) of Law Number 22 of 2009 concerning Traffic and Road Transportation (hereinafter referred to as UULLAJ) regulates the turning on of headlights for motorcyclists during the day. This research is a sociological legal research. The location of this research was conducted at the Pekanbaru Police. The results of this research are first to implement Article 107 Paragraph (2) of Law No. 22 of 2009, including, warnings to motorists carried out by the Pekanbaru Traffic Police by conducting raids on the highway centered on certain posts, and conducting patrols to the public passing through Pekanbaru City. Keywords: Law Enforcement, Headlights, Motorcycles